2021
DOI: 10.1186/s40708-021-00133-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating deep learning EEG-based mental stress classification in adolescents with autism for breathing entrainment BCI

Abstract: Mental stress is a major individual and societal burden and one of the main contributing factors that lead to pathologies such as depression, anxiety disorders, heart attacks, and strokes. Given that anxiety disorders are one of the most common comorbidities in youth with autism spectrum disorder (ASD), this population is particularly vulnerable to mental stress, severely limiting overall quality of life. To prevent this, early stress quantification with machine learning (ML) and effective anxiety mitigation w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 93 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…Although MI-EEGNET performed better than previous architectures, the high number of trainable parameters made it challenging to interpret. Besides these CNN architectures investigated for EEG signal classification, several studies can be found in the literature that used recurrent neural network (RNN) and its variants [21][22][23], such as LSTM and gated recurrent units (GRU), for the classification of mental tasks based on EEG signals [24,25]. However, RNNs are less prevalent in this area due to their exploding/vanishing gradient or lack of memory problems [26].…”
Section: Related Workmentioning
confidence: 99%
“…Although MI-EEGNET performed better than previous architectures, the high number of trainable parameters made it challenging to interpret. Besides these CNN architectures investigated for EEG signal classification, several studies can be found in the literature that used recurrent neural network (RNN) and its variants [21][22][23], such as LSTM and gated recurrent units (GRU), for the classification of mental tasks based on EEG signals [24,25]. However, RNNs are less prevalent in this area due to their exploding/vanishing gradient or lack of memory problems [26].…”
Section: Related Workmentioning
confidence: 99%
“…Ref. [31] 5 Classification: Adaptive neurofuzzy inference system (ANFIS), and also its variants with grasshopper optimization algorithm (ANFIS-GOA), particle swarm optimization (ANFIS-PSO), and breeding swarm optimization (ANFIS-BS).…”
Section: Asd Classification/detectionmentioning
confidence: 99%
“…In reference [30], they used an ML and a DL process for diagnosing ASD from time-frequency spectrogram images of EEG. The authors in [31] reported that it is possible to evaluate mental stress using DL and EEG records. There are also studies such as [32], where they used the free artifact signal of two electrodes to detect ASD.…”
Section: Introductionmentioning
confidence: 99%
“…When deep learning becomes the consensus and normal state of educational practice and the essence of learning returns, the name of “deep learning” may return to “learning” instead of emphasizing “depth”. It is worth mentioning that deep learning is relative to false learning and mechanical learning, and the latter two are not what school teaching should be ( Sakalle et al, 2021 ; Sundaresan et al, 2021 ). Each computing layer of the network is composed of multiple feature maps, and each feature map exists in the form of a two-dimensional plane.…”
Section: Deep Learning Researchmentioning
confidence: 99%